Association Between Vitamin D Receptor Gene Polymorphism rs2228570 and Allergic Rhinitis - Zhang W; Xu Y (Dove Medical Press, 2020)
Wei Zhang,1 Yu Xu1,2 1Department of Otolaryngology Head and Neck Surgery, Renmin Hospital of Wuhan University, Wuhan, Hubei Province, People’s Republic of China; 2Research Institute of Otolaryngology Head and Neck Surgery, Renmin Hospital of Wuhan University, Wuhan, Hubei Province, People’s Republic of ChinaCorrespondence: Yu XuDepartment of Otolaryngology Head and Neck Surgery, Renmin Hospital of Wuhan University, No. 238 Jiefang Road, Wuhan, Hubei Province 430060, People’s Republic of ChinaTel +86-02788041919Email 3025482437@qq.comBackground: Vitamin D receptor (VDR) gene polymorphisms are involved in a variety of immune-related diseases, and VDR is associated with allergic rhinitis. The present study explored the associations between VDR gene polymorphisms and allergic rhinitis in the Chinese population.Methods: The study population consisted of 400 patients with allergic rhinitis and 400 healthy controls. General characteristics were determined by interview. Blood DNA was extracted and genotyping was performed via matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. The associations of each genetic variant with risk for AR were assessed by calculating the odds ratio (OR) with 95% confidence interval (95% CI).Results: No significant differences were observed in general characteristics between cases and controls. The distributions of genotypes at the rs2228570 locus of the VDR gene conformed to Hardy–Weinberg equilibrium. There was a significant difference in the distribution of rs2228570 genotype (P< 0.001) between cases and controls. Compared to GG and GA genotypes, the AA genotype increased the risk of AR (OR=3.27, 95% CI: 2.10– 5.11, P=0.000; OR=2.58, 95% CI:1.63– 4.08, P< 0.001). Similar results were also observed in the dominant model (OR=1.64, 95% CI:1.24– 2.17, P< 0.001) and codominant model (OR=2.95, 95% CI:1.93– 4.51, P< 0.001). The A allele was still associated with elevated risk gene for AR after adjusting for potential confounding factors. Subgroup analyses indicated an interaction between alcohol and rs2228570 in the risk of allergic rhinitis. The A allele also increased the risk for AR in the population without asthma (OR=1.85, 95% CI:1.46– 2.34, P< 0.001).Conclusion: VDR gene polymorphism is associated with AR, and the AA genotype of rs2228570 is associated with the increased risk of AR in the Chinese population.Keywords: allergic rhinitis, gene polymorphism, case–control, vitamin D receptor